MACROECONOMIC IMPACT ON STOCK PRICE VOLATILITY: EVIDENCE FROM UK AND US - Yu, Qing (2012)
The objective of the study is to investigate the relationship between macroeconomic variables and the stock market index for UK and US in London Stock Exchange (LSE) and New York Stock Exchange (NYSE) by carrying out the Ordinary Least Square (OLS) multiple regression for the period of eleven years from February 2001 up to November 2011. In this study, we consider the quarterly data of six macroeconomic variables which are: interest rate, foreign exchange rate & reserve, gross fixed capital formation, money supply, inflation, and industrial production respectively. Due to the uniqueness of the sample period which contains the financial crisis and recession period, the study intend to find the effect of the crisis on the stock market, hence, a dummy variable Crisis (CR) is added to the regression. However, the financial crisis only has significant influence on the US stock market, while no significant relationship is found for the UK stock market.This study extends approach by focusing on the performance of the stock market as a whole and comparing the effects of the movements in the two different economies of UK and US on the fluctuations in stock prices. The results of the regression analysis indicate that the UK stock price volatility is significantly positively related to interest rate, money supply and industrial production index, while exchange rate, inflation rate and gross fixed capital formation can significantly negatively affect the UK stock market index. As for the US stock index, it is discovered to be significantly positively related to interest rate, foreign exchange rate & reserves and money supply, and only gross fixed capital formation significantly negatively contributes to the changes in the US stock index. Both of the UK and US model have strong explanatory power of the detected significant determinants in explaining the changes in the macro-economies. The empirical results of this study could be used as valuable information for local and global stock investors who seek an investment opportunity in the UK and US stock markets.